Reciprocal functional interactions between the brainstem and the lower spinal cord - Yazawa, Itaru (Frontiers in Neuroscience, 2014)
The interplay of the neuronal discharge patterns regarding respiration and locomotion was investigated using electrophysiological techniques in a decerebrate and arterially perfused in situ mouse preparation. The phrenic, tibial and/or peroneal nerve discharge became clearly organized into discharge episodes of increasing frequency and duration, punctuated by periods of quiescence as the perfusion flow rate increased at room temperature. The modulated sympathetic tone induced by the hyperoxic/normocapnic state was found to activate the locomotor pattern generator (LPG) via descending pathways and generate a left and right alternating discharge during discharge episodes in the motor nerves. The rhythm coupling of respiration and locomotion occurred at a 1:1 frequency ratio. Although the phrenic discharge synchronized with the tibial discharge at all flow rates tested, the time lag between peaks of the two discharges during locomotion was ≈400 ms rather than ≈200 ms, suggesting spinal feedback via ascending pathways. The incidence of the phrenic and tibial discharge episodes decreased by ≈50% after spinalization at the twelfth thoracic vertebra and the respiratory rhythm was more regular. These results indicate that: (i) locomotion can be generated in a hyperoxic/normocapnic state induced by specific respiratory conditions, (ii) the central mechanism regarding entrainment of respiratory and locomotor rhythms relies on spinal feedback via ascending pathways, initiated by the activated LPG generating locomotion, and (iii) the increase in respiratory rate seen during locomotion is caused not only by afferent mechanical and nociceptive inputs but also by impulses from the activated spinal cord producing a locomotor-like discharge via ascending pathways.